PENGARUH KONFLIK KERJA, KEPEMIMPINAN, DAN LINGKUNGAN KERJA TERHADAP STRESS KERJA PEGAWAI - Melinda Pratiwi Hartomo; Surahman Pujianto (SINERGI : Jurnal Riset Ilmiah, 2026)
PT. KMB is a company that cultivates oil palm plants and processes them into CPO. PT. KMB follows government regulations, but in reality, it does not comply with government regulations regarding overtime hours. Happy Prosperous Works. The purpose of this study was to determine the effect of work conflict on employee work stress at PT. KMB, the influence of leadership on employee work stress at PT. KMB, and knowing the effect of the work environment on employee work stress at PT. KMB. The research design used in this study is a descriptive research design and causality research. The result of the research is that there is an influence between work conflict and work stress at PT. KMB. This can be seen from the t-value of 2,458 > t-table of 1.976 and the sig value of 0.015 < 0.05. Then there is no influence between leadership and work stress at PT. KMB. This can be seen from the t-value of 1,863 < t-table of 1.976 and the sig value of 0.064 > 0.05. In addition, there is no influence between the work environment and work stress at PT. KMB. This can be seen from the calculated -t value – 1,768 > -t table -1.976 and the sig value of 0.079 > 0.05.